Pengaruh Digital Influencer Pada Penggunaan Labeling “Tasya Farasya Approved” Terhadap Minat Beli Luxcrime Ultra Light Lip Stain - Mia Risti Amalia; Samaria, Sarah (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2025)
Technological developments in the world of social media have had a significant impact on digital marketing, particularly in the cosmetics industry with the use of digital influencers. The digital influencer approach has become a force capable of influencing customer preferences and purchasing intentions. The focus of this study analyzes the influence of digital influencers on the use of the "Tasya Farasya approved" labeling on purchasing intentions. This study uses a quantitative approach and involves 100 respondents selected through a purposive sampling technique. Data were collected through a questionnaire distributed via Google Form with validity and reliability tests. Data analysis revealed a moderate relationship between digital influencers and purchasing intentions. Therefore, the results of this study, based on hypothesis testing and coefficient of determination tests, state that the digital influencer variable has a significant influence on purchasing intentions. Thus, the marketing strategy of collaborating with digital influencers on the use of the "Tasya Farasya approved" labeling on Instagram is an effective strategy to influence purchasing intentions for the Luxcrime Ultra Light Lip Stain product.